Plant products for pharmacology: application of enzymes in their transformations - Zarevúcka, Marie; Wimmer, Zdeněk (International journal of molecular sciences, 2008)
Different plant products have been subjected to detailed investigations due to their increasing importance for improving human health. Plants are sources of many groups of natural products, of which large number of new compounds has already displayed their high impact in human medicine. This review deals with the natural products which may be found dissolved in lipid phase (phytosterols, vitamins etc.). Often subsequent convenient transformation of natural products may further improve the pharmacological properties of new potential medicaments based on natural products. To respect basic principles of sustainable and green procedures, enzymes are often employed as efficient natural catalysts in such plant product transformations. Transformations of lipids and other natural products under the conditions of enzyme catalysis show increasing importance in environmentally safe and sustainable production of pharmacologically important compounds. In this review, attention is focused on lipases, efficient and convenient biocatalysts for the enantio- and regioselective formation / hydrolysis of ester bond in a wide variety of both natural and unnatural substrates, including plant products, eg. plant oils and other natural lipid phase compounds. The application of enzymes for preparation of acylglycerols and transformation of other natural products provides big advantage in comparison with employing of conventional chemical methods: Increased selectivity, higher product purity and quality, energy conservation, elimination of heavy metal catalysts, and sustainability of the employed processes, which are catalyzed by enzymes. Two general procedures are used in the transformation of lipid-like natural products: (a) Hydrolysis/alcoholysis of triacylglycerols and (b) esterification of glycerol. The reactions can be performed under conventional conditions or in supercritical fluids/ionic liquids. Enzyme-catalyzed reactions in supercritical fluids combine the advantages of biocatalysts (substrate specificity under mild reaction conditions) and supercritical fluids (high mass-transfer rate, easy separation of reaction products from the solvent, environmental benefits based on excluding organic solvents from the production process).
Keywords: phytosterol; esterification; hydrolysis; plant oil; Lipase; ionic liquid; supercritical fluid